Circulating cardiovascular microRNAs in critically ill COVID‐19 patients. (5th March 2021) - Garg, Ankita; Seeliger, Benjamin; Derda, Anselm A.; Xiao, Ke; Gietz, Anika; Scherf, Kristian; Sonnenschein, Kristina; Pink, Isabell; Hoeper, Marius M.; Welte, Tobias; Bauersachs, Johann; David, Sascha; et al.
Abstract: Aims: Coronavirus disease 2019 (COVID‐19) is a still growing pandemic, causing many deaths and socio‐economic damage. Elevated expression of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) entry receptor angiotensin‐converting enzyme 2 on cardiac cells of patients with heart diseases may be related to cardiovascular burden. We have thus analysed cardiovascular and inflammatory microRNAs (miRs), sensitive markers of cardiovascular damage, in critically ill, ventilated patients with COVID‐19 or influenza‐associated acute respiratory distress syndrome (Influenza‐ARDS) admitted to the intensive care unit and healthy controls. Methods and results: Circulating miRs (miR‐21, miR‐126, miR‐155, miR‐208a, and miR‐499) were analysed in a discovery cohort consisting of patients with mechanically‐ventilated COVID‐19 ( n  = 18) and healthy controls ( n  = 15). A validation study was performed in an independent cohort of mechanically‐ventilated COVID‐19 patients ( n  = 20), Influenza‐ARDS patients ( n  = 13) and healthy controls ( n  = 32). In both cohorts, RNA was isolated from serum and cardiovascular disease/inflammatory‐relevant miR concentrations were measured by miR‐specific TaqMan PCR analyses. In both the discovery and the validation cohort, serum concentration of miR‐21, miR‐155, miR‐208a and miR‐499 were significantly increased in COVID‐19 patients compared to healthy controls. Calculating the area under the curve using receiver operating characteristic analysis miR‐155, miR‐208a and miR‐499 showed a clear distinction between COVID‐19 and Influenza‐ARDS patients. Conclusion: In this exploratory study, inflammation and cardiac myocyte‐specific miRs were upregulated in critically ill COVID‐19 patients. Importantly, miR profiles were able to differentiate between severely ill, mechanically‐ventilated Influenza‐ARDS and COVID‐19 patients, indicating a rather specific response and cardiac involvement of COVID‐19. Abstract : Circulating levels of inflammation and cardiac myocyte‐specific miRs are dysregulated in the blood of critically ill COVID‐19 patients compared to healthy individuals and also severely ill Influenza‐ARDS patients.